APPLICATION OF TOURISM RETRIBUTION POLICY AT GUNUNG ANYAR MANGROVE BOTANICAL GARDEN SURABAYA - Fadilla Zafira; Oktarizka Reviandani (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the implementation of the tourism retribution policy at Kebun Raya Mangrove Gunung Anyar Surabaya and its contribution to local revenue. The research employs Edward III (1980) policy implementation model, which includes four key variables: communication, resources, disposition, and bureaucratic structure. A qualitative descriptive approach was applied, with data collected through observation, interviews, and documentation. The findings indicate that the policy has been successfully implemented as an administrative and fiscal triumph, generating a total revenue of IDR 1.55 billion within its first two years. In terms of communication, the policy has achieved high procedural transparency through clear physical signage and a robust digital strategy via social media platforms like TikTok and Instagram. From the resource aspect, the institutionalization of e-ticketing and QRIS systems has significantly enhanced financial accountability. Regarding disposition, the management shows exceptional commitment to municipal fiscal targets, supported by a bureaucratic structure that functions as a “fortress of integrity” through the disciplined execution of SOP No. SOP/KRMS/01/2025. However, challenges remain regarding the decline in visitor numbers and the severe economic impact on local SMEs, who experienced a 50-70% revenue loss. This study concludes that while the policy is as resounding financial success, its long-term sustainability depends on shifting toward a more service-oriented and inclusive management style that prioritizes stakeholder welfare and routine infrastructure maintenance.